Perancangan Mobile Sample Preparation Unit Dengan Model Process Lay Out - Girman Sihombing; Evy Priyanti; Nining Suryani (IMTechno: Journal of Industrial Management and Technology, 2023)
One of the most important activities in Mining industry is the exploration step, Because the result of this activities will be as a basis of taking a decision about the continuity of mining activities in the future. This step must give the accuracy of information about the mineral content and the geological condition where the mining activity is done. The sample preparation is one of the parts of laboratory activities in exploration step. This activity is the first process before analyzing the sample content, so that this process must be organized and controlled as well for getting high quality final analysis result which is based on its precision and accuracy value. In getting the precision and accuracy of value content in the sample, the beginning process until finish in the laboratory activities must be assured that no value interference from the other source or other sample. The Mobile Sample Preparation Unit (MSPU) is one of the designs which can be applied in remote area where the exploration activities are done.